1996
DOI: 10.1007/s002329900003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Whole Cell Chloride Conductances in a Mouse Inner Medullary Collecting Duct Cell Line mIMCD-3

Abstract: The chloride conductance of inner medullary collecting duct cells (mIMCD-3 cell line) has been investigated using the whole cell configuration of the patch clamp technique. Seventy-seven percent of cells were chloride selective when measured with a NaCl-rich bathing solution and a TEACl-rich pipette solution. Seventy-five percent of chloride-selective cells (90/144) had whole cell currents which exhibited an outwardly-rectifying (OR) current-voltage (I/V) relationship, while the remaining cells exhibited a lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…1e). This resulted in a mean shift in E rev of 16.4±2 mV, giving a P Cation /P Cl of 0.25 (n=3), similar to that which has previously been reported for I CLCA [28,31], indicating that the zinc-stimulated whole-cell current was predominantly Cl − selective. Next, the sensitivity of I CLCA to extracellular zinc was investigated.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…1e). This resulted in a mean shift in E rev of 16.4±2 mV, giving a P Cation /P Cl of 0.25 (n=3), similar to that which has previously been reported for I CLCA [28,31], indicating that the zinc-stimulated whole-cell current was predominantly Cl − selective. Next, the sensitivity of I CLCA to extracellular zinc was investigated.…”
Section: Resultssupporting
confidence: 76%
“…We now show that I CLCA is stimulated by extracellular zinc. Under basal conditions, 74% of cells (64/87) displayed whole-cell currents, which were outwardly rectifying and time independent at voltages between −100 and +80 mV similar to I CLCA previously reported in this cell line [28,31]. Addition of ZnCl 2 (400 μM) to the bath solution resulted in an increase in whole-cell current density at ±60 mV, reaching a plateau after 5 min, which was partially reversible after the removal of ZnCl 2 from the bathing solution (Fig.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…We are using a mouse inner medullary cell line (mIMCD-3) as an appropriate model to study the Clconductances in this nephron segment. Our previous studies, using the fast whole-cell configuration of the patch-clamping technique, showed that 78 % of cells studied had substantial resting basal Cl-conductances (Shindo et al 1996), similar to those seen in other secretory cells after secretagogue stimulation. The purpose of this report was to determine if the high basal conductances in mIMCD3 cells were due to the loss of intracellular factors that occurs with this method.…”
supporting
confidence: 62%
“…Thus activation of this conductance will directly promote entry/exit of anions from the tubule lumen. It is likely that there is a finite permeability of this conductance even to large organic anions such as gluconate [7]. The CLCA protein is a novel candidate for modulation of the milieu of the collecting duct, and its dysregulation may lead to stone formation.…”
Section: Ca-sensing and Ca-activated Anion Conductancesmentioning
confidence: 99%